ANALYSIS OF PROPERTIES OF CONCRETE USING SHEEP WOOL DIPPING IN SALT WATER AS FIBRE REINFORCEMENT ADMIXTURE - Gadgihalli, Vishal; Y.R, Meena; Chandana; Dinakar, Prasad Havanje (International Journal of Research -GRANTHAALAYAH, 2017)
The use of admixtures is increasing very rapidly because concrete admixtures provide physical as well as economic benefits. These admixtures materials ranged from blood in history to recent fiber reinforcement. In this paper analysis of properties of concrete using salt water cored and oven dried sheep wool as fiber reinforced admixture was studied and verified the strength of concrete compared to ordinary Portland cements strength of different grade of concrete using sheep wool as fiber reinforcement admixtures. Using sheep wool as fiber reinforcement as concrete admixture gave good percentage of increment in both compressive strength and flexural strength of concrete, but as the grade of cement increases the percentage of increment in strength gradually reduces.